Surface formation and modification in electrical discharge machining - Ahmed, Shamraze (2022)
Electrical discharge machining (EDM) is a non-conventional machining process predominately used to machine hard materials that are difficult to machine using conventional processes. Material removal is through a non-contact thermally driven process utilising electrical discharges. One drawback of EDM is the formation of a recast surface which can affect part properties. Oxide layers are sites of potential cracks, are brittle, are prone to spalling, potentially contributing to premature part failure, have lower melting temperatures, are porous and loose, and are difficult to control. These recast layer defects must be controlled via lengthy parameter optimisation or removed post-process, where surface integrity is critical.. The recast layer has been studied extensively; however, oxides have not been studied in depth, only through observations or brief discussions as part of other works. The thesis first aims to understand EDM recast oxide formation and propose a route to reduce oxides. By altering parameters, the aim is to alter discharge energy and discharge/crater formation characteristics, as well as cooling and flushing of the spark gap. This showed that current, on-time and discharge energy lead to increased oxides, while off-time and pressure decreased oxides, which was linked to differences in gas, molten crater, and gap characteristics, and explored via constant energy experiments. This showed the importance of parameter discharge impulse force, which alters ejection and oxidation behaviour. Therefore, to achieve a feature with low amounts of oxides, a shorter on-time and lower discharge energy is needed, as well as increased flushing and off-time. This results in a parameter with high discharge impulse and high gap flushing and cooling. Electrochemical methods have been used to remove recast post-process, however limited work has been done in combining EDM and ECM in a single process. A method to produce a zero-recast surface in a single controllable process, in a single step, combining the accuracy of EDM with the surface finish of ECM, has been proposed in this thesis. Electrochemical dissolution was used to remove the recast layer while electrical discharges were used to advance hole depth. The expansion of the side wall enables EDM to occur only on the frontal area, while ECM is limited on the side, thus creating discrete electrolytic and dielectric zones. To control dissolution dielectric electrical conductivity was altered and to control dissolution mechanisms type of salt additive was changed. NaCl produced a pitted surface while NaHCO3 produced a surface with passive oxides with limited recast removal. NaNO3 and NaNO2 produced zero-recast surfaces, however with regions of excessive electrochemical pitting and removal. Finally, Na2SO4 and Na2SO3 produced smooth surfaces with removed recast, with Na2SO3 removing the recast through controlled electro-polishing. The preferred surface and most controllable electrolytic-dielectric was found to be Na2SO3. To understand the balance between the EDM and ECM parts of the process, pulse waveform analysis must be conducted. The process was split into four pulse types and their significance explained: electrical discharge, semi-arc discharge, delayed discharge, and electrochemical. Intervals of high-voltage, when using DI, would result in regions of ECM when conductivity was increased. The EDM:ECM balance was crucial to process understanding and was directly affected by the high voltage intervals which occur due to gap conditions. The electrochemical difference between electrolytic-dielectrics was shown through the EDM:ECM pulse ratio and gas analysis, showing that NaCl, which is the most aggressive salt, has the most ECM pulses, while NaHCO3 which is the least aggressive has the most EDM pulses. Differences in electrolytic-dielectrics were explained due to dissolution mechanisms and pulse charge, which increase the high voltage intervals and ECM pulses. Similarly, an increase in conductivity and depth increases ECM pulses and charge, hindering EDM pulses. A mathematical model was used to illustrate the overall process balance through fundamental electrochemical theory and process pulse data. Through this model, the point during machining at which complete recast layer removal occurs is predicted and validated through experimental analysis.